Eucalyptus ESTs related to genes for oxidative stress - Alves, E.; Velini, Edivaldo Domingues [UNESP]; Trindade, MLB; Cataneo, A. C.; Marino, C. L.; Mori, Edson Seizo [UNESP]; Guerrini, L. A.; Furtado, Edson Luiz [UNESP]; Wilcken, Carlos Frederico [UNESP] (Marcel Dekker Inc, 2005)
Oxidative stress generating active oxygen species has been proved to be one of the underlying agents causing tissue injury after the exposure of Eucalyptus (Eucalyptus spp.) plants to a wide variety of stress conditions. The objective of this study was to perform data mining to identify favorable genes and alleles associated with the enzyme systems superoxide dismutase, catalase, peroxidases, and glutathione S-transferase that are related to tolerance for environmental stresses and damage caused by pests, diseases, herbicides, and by weeds themselves. This was undertaken by using the eucalyptus expressed-sequence database (https//forests.esalq.usp.br). The alignment results between amino acid and nucleotide sequences indicated that the studied enzymes were adequately represented in the ESTs database of the FORESTs project.
Keywords: genome; antioxidant enzymes